Respuesta :

The answer:  " x = 68, y = 72 " .
____________________________
Explanation:
________________________________________
46 + (x - 3) + (y - 3) = 180 .

46 + 1(x - 3) + 1(y-3) = 180 .

46 + 1x - 3 + 1y - 3 = 180 .

46 - 3 - 3 + 1x + 1y = 180 .

40 + x + y = 180 ;

Subtract "40" from EACH SIDE of the equation:
______________________________________
 40 + x + y - 40 = 180 - 40 ;

 to get:

x + y = 140 ;
_____________________________________
Now:
_____________________________________
65 = (x - 3) ;


↔  x - 3 = 65 ;

Add "3" to EACH SIDE of the equation;

    x - 3 + 3 = 65 + 3 ;

to get:
 
           x = 68 .
______________________________
Now:

Since:  "x + y = 140" ;

Let us plug in our known value, "68" ;  for "x" ;

to solve for "y" ;
__________________________________
   x + y = 140 ;
 
  68 + y = 140 ;

↔ y + 68 = 140 ;

Subtract "68" from EACH SIDE of the equation; to isolate "y" on one side of the equation; and to solve for "y" ;
______________________________________________
   y + 68 - 68 = 140 = 68 ;

                  y = 72 .
______________________________________________
So,  solve for "x" and "y".

x = 68, y = 72 .
_______________________________________________

Answer:

The answer:  " x = 68, y = 72 " .

Step-by-step explanation: